Dampak Daya Tarik Dan Fasilitas TerhadapKeputusan Berkunjung Wisata HalalKota Padang - Reza Dwi Aspita; Sophan Sophian (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The purpose of this study was to examine the impact of attractions and facilities on the decision to visit Halal Tourism in Padang City. This type of research uses quantitative methods. Data collection through distributing questionnaires to 108 respondents using accidental sampling technique. By using instrument testing (validity test and reliability test), classic assumption test (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and hypothesis testing with the help of the SPSS application. The results of this study indicate that attractiveness has a positive and significant effect on the decision to visit, and facilities have a positive and significant effect on the decision to visit. So it can be concluded in this study that it was found that the variables of attractiveness and facilities had a positive and significant effect on the decision to visit Halal Tourism in Padang City.